Studies on the low-temperature damage in rice [Oryza sativa] seedlings: Effect of low temperature on the growth and bleeding rates of the root - Yang, Z. (Kagoshima Univ. (Japan). Faculty of Agriculture); Sasaki, O; Shimotashiro, T; Nakagama, A (Japanese journal of crop science, 2001)
In Hunan Province in China, where double cropping of Indica rice is common, low-temperature damage on seedlings during the nursery period becomes a main problem in the first cropping. We examined the effect of low temperatures (8, 11 and 14degC) on the root growth and the bleeding rate of the seedlings during raising stage. Indica (Zhe9248, Xiang24) , Japonica 1 (Koshihikari) and Japonica 2 (Tanshinwase, Hayayuki), which are characterized by their different low-temperature resistances, were used. The root growth and the bleeding rates of Indica and Japonica 1 were always inferior to those of Japonica 2 at each low temperature tested. In particular, it was noted that the bleeding rates of Indica and Japonica 1 have decreased promptly at treatment under 11degC, but the bleeding rate of Japonica 2 was relatively high even at 8degC. It showed that the root growth and bleeding rate of the plants tested recovered when they were reset to the normal temperature (20degC). The recoveries of the root growth and bleeding rate of Japonica 2 were higher than those of Indica and Japonica 1. The degrees of recovery in both traits revealed their close relationship with the quantity of bleeding rate under the preceding low-temperature condition. Based on these results, the low-bleeding rate under the low temperature may be responsible for the inferior recovery of the root growth and the bleeding rate of Indica and Japonica 1 in comparison to Japonica 2.